Taxonomic Revision of Lipoptilocnema (Diptera: Sarcophagidae), With Notes on Natural History and Forensic Importance of Its Species - Mulieri, Pablo Ricardo (2017)
Lipoptilocnema Townsend is a small genus of Neotropical Sarcophaginae with a distinctive genitalic morphology. This genus is revised based on the examination of the type series and large numbers of specimens of the seven previously known species, plus three new ones herein described, one from Argentina (L. delfinado Mulieri and Mello-Patiu, sp. nov.), and two from Brazil (L. savana Mulieri and Mello-Patiu, sp. nov. and L. tibanae Mulieri and Mello-Patiu, sp. nov.). All species are described or redescribed and illustrated. Distribution maps and a key for male identification are provided. The taxonomic position of this genus is reviewed and the interpretation of phallic structures is discussed. Notes on the natural history of Lipoptilocnema species are provided, and their potential importance as PMI indicators is highlighted, including the first record of Lipoptilocnema reared from a dead human body.